A stepwise synthetic approach and antibacterial assessment of some new pyrazoline derivatives containing azo and benzyloxy moieties - Daryan O. Ali; Farouq E. Hawaiz (Zanco Journal of Pure and Applied Sciences, 2023)
This study has designed an efficient stepwise reaction to produce some new pyrazoline derivatives bearing azo and benzyloxy linkages. The reaction was initiated by diazotizing p-aminocetophenone with 2,6-dichlorophenol to give azo compound (1), which was further reacted with benzyl bromide producing the efficacious core material azo-benzyloxy acetophenone(2). This study has designed an efficient stepwise synthesis to produce some new pyrazoline derivatives that contains azo and benzyloxy linkages. The Synthesis route was initiated by diazotizing p-aminocetophenone with 2,6-dichlorophenol to give azo compound (1), which was then reacted with benzyl bromide producing the efficacious core material azo-benzyloxy acetophenone (2). Moreover, compound (2) was treated with a series of substituted benzaldehydes to form intermediate chalcone derivatives (3a-j) which were then treated with phenylhydrazine via Michael type addition reaction to form azo-benzyloxy pyrazoline molecules (4a-j). Ultimately, the structures of the synthesized compounds were revealed using spectroscopic techniques: FT-IR, 1H-NMR, 13C-NMR, and 13C-DEPT-135 spectra. Antimicrobial activities were screened for synthezied Azo-chalcones and Pyrazolines against S.aureus as gram-positive and E.Coli as gram-negative in comparison to a standard antibiotic drug Azithromycine